Thyroid Associated Ophthalmopathy: A Review - P.S, Mallika; Tan , A.K; Aziz, S.; Syed Alwi, S.A.R; Chong, M.S; R., Vanitha; G, Intan (Academy of Family Physicians of Malaysia, 2009)
Thyroid associated ophthalmopathy is an autoimmune disorder affecting the orbital and periorbital tissues. Hyperthyroidism is commonly associated with thyroid associated ophthalmopathy, however in 5% to 10% of cases it is euthyroid. Genetic, environmental and endogenous factors play a role in the initiation of the thyroid ophthalmopathy. Smoking has been identified as the strongest risk factor for the development of the disorder. The pathogenesis involves activation of both humoral and cell mediated immunity with subsequent production of gycoaminoglycans, hyaluronic acid resulting in oedema formation, increase extraocular mass and adipogenesis in the orbit. The natural history of the disease progresses from active to inactive fibrotic stage over a period of years. Diagnosis is mainly clinical and almost all patients with ophthalmopathy exhibit some form of thyroid abnormality on further testing. Treatment is based on the clinical severity of the disease. Non-severe cases are managed by supportive measures to reduce the symptomatology and severe cases are treated by either medical or surgical decompression. Rehabilitative surgery is done for quiescent disease to reduce diplopia and improve cosmesis.